2019
DOI: 10.3389/fimmu.2018.03099
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA Profiles as a Potential Biomarker in Differentiating Adult-Onset Still's Disease From Sepsis

Abstract: Adult-onset Still's disease (AOSD) is a systemic inflammatory disease characterized by cytokine storm. However, a diagnostic test for AOSD in clinical use is yet to be validated. The aim of our study was to identify non-invasive biomarkers with high specificity and sensitivity to diagnosis of AOSD. MicroRNA (miRNA) profiles in PBMC from new-onset AOSD patients without any treatment and healthy controls (HCs) were analyzed by miRNA deep sequencing. Plasma samples from 100 AOSD patients and 60 HCs were used to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…In a previous study, we first screened the susceptibility of genetic factors in AOSD using a genome-wide association study and revealed that the SNPs rs3115628 (HLA class I region) and rs9268832 (HLA class II region) were strongly associated with AOSD in the Chinese population (4). Moreover, we identified plasma microRNA profiles using microRNA sequencing in patients with AOSD (12). In the current study, we further explored the urine proteomics of AOSD by iTRAQ-labeling combined with LC-MS/MS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we first screened the susceptibility of genetic factors in AOSD using a genome-wide association study and revealed that the SNPs rs3115628 (HLA class I region) and rs9268832 (HLA class II region) were strongly associated with AOSD in the Chinese population (4). Moreover, we identified plasma microRNA profiles using microRNA sequencing in patients with AOSD (12). In the current study, we further explored the urine proteomics of AOSD by iTRAQ-labeling combined with LC-MS/MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen-associated molecular patterns or danger-associated molecular patterns trigger inflammasome activation and the production of interleukin 1β (IL-1β) and IL-18, further improving the expression of the proinflammatory cytokines tumor necrosis factor α (TNF-α) and IL-6 and the anti-inflammatory cytokines IL-10 and IL-37 ( 1 , 6 , 7 ). Additionally, a markedly high frequency of elevated serum molecules such as alarmins (S100A8/A9 and S100A12), chemokines (C-X-C motif chemokine ligand 9, 10, and 11), and microRNAs, which correlate with disease activity, was noticed in patients with AOSD ( 8 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Routine inflammatory markers, cytokines, and several molecules reflecting innate immune activation are increased in patients with AOSD and used in clinical practice (20). Our previous study demonstrated that a combined microRNAs (miRNAs) panel in plasma could be a non-invasive biomarker for the diagnosis of AOSD and to differentiate it from sepsis, providing some evidences in the study of biomarkers in AOSD (21). However, biomarkers with high specificity and sensitivity for diagnosis of AOSD organ involvement is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory response then indirectly stimulates the production rate of the energetic (E) response (K inE ) and the production rate of the anti-inflammatory (A) response (K inA ). The energetic response stimulates both pro-inflammation and antiinflammation, while anti-inflammation serves as the immuno-regulatory component of the system by restoring intracellular homeostasis post-transcriptional regulatory mechanism for gene expression in many cellular processes, including the immune response, as well as playing a crucial role in the endotoxin tolerance system [34][35][36][37][38][48][49][50]. For example, when miR146, miR155 and miR125b are stimulated by LPS in human monocytic cells [51][52][53], they can inhibit TLR4/IL-1R signaling via the post-transcriptional regulation of signaling proteins such as IL-1 receptor-associated kinase 1 (IRAK-1) and TNF receptor-associated factor 6 (TRAF6) [49,53].…”
Section: Numerical Modelmentioning
confidence: 99%
“…In order to consider the increasing importance of epigenetic regulation (including microRNA; miRNA) in sepsis [34][35][36][37][38], the objective of the present study was to improve the model proposed by Calvano et al [28] by adding epigenetic regulatory loops. Moreover, we aimed to obtain further insights into the therapeutic options for modifying the pro-/anti-inflammatory balance by including a pharmacology modeling stratum.…”
Section: Introductionmentioning
confidence: 99%